EXTH-44. ADDITION OF THE CARBONIC ANHYDRASE IX INHIBITOR SLC-0111 TO TEMOZOLOMIDE EXTENDS SURVIVAL OF MICE BEARING ORTHOTOPIC GLIOBLASTOMAS. Issue 11 (6th November 2017) - Boyd, Nathaniel; Walker, Kiera; Tran, Anh; Hackney, James; McDonald, Paul; Benavides, Gloria; Bevensee, Mark; Gillespie, Yancey; Nabors, Burt; Darley-Usmar, Victor; Dedhar, Shoukat; Hjelmeland, Anita
Abstract: Brain tumor microenvironments characterized by hypoxia, restricted glucose, and acidic stress contain a subset of neoplastic cells that thrive in these environments, identified as brain tumor initiating cells (BTICs). BTICs are resistant to chemo- and radiotherapy, providing a reservoir for tumor recurrence and a desirable target for glioma treatments. Standard of care for glioblastoma (GBM) includes surgical resection, radiation therapy, and the chemotherapeutic agent temozolomide, which prolongs life expectancy by months and is not curative. Prior studies suggested the efficacy of chemotherapies including temozolomide was increased by reducing expression of carbonic anhydrase 9 (CA9). CA9 is a hypoxia responsive gene elevated in tumors that is important for regulating intracellular pH and contributing to the acidic extracellular microenvironment. After confirming basal and hypoxia-induced expression of CA9 in GBM BTICs, we targeted CA9 activity with the small molecule inhibitor SLC-0111 alone or in combination with temozolomide. In multiple GBM BTIC lines, SLC-0111 reduced cell growth in vitro and showed additional benefit when used concurrently with temozolomide. Mechanistically, SLC-0111 treatment increased temozolomide DNA damage and resulted in changes to cellular metabolism and pH. SLC-0111 decreased the enrichment of BTICs after temozolomide treatment as determined via BTIC marker expression and functionally with neurosphere formation. SLC-0111 was detected in the brain after oral gavage administration of a formulation in Phase I clinical trials for breast cancer patients. SLC-0111 and temozolomide also significantly reduced the growth of subcutaneous and orthotopic models of a recurrent GBM greater than either drug alone. Together, our data suggest that SLC-0111 can sensitize GBM BTICs to the chemotherapy temozolomide and extend animal survival.